2009
DOI: 10.1073/pnas.0810094106
|View full text |Cite
|
Sign up to set email alerts
|

Src phosphorylation of RhoGDI2 regulates its metastasis suppressor function

Abstract: RhoGDI2 is a suppressor of metastasis in human bladder cancer. Although diminished RhoGDI2 expression in tumors is associated with decreased patient survival, normal expression in some metastatic tumors led us to wonder whether other mechanisms regulate RhoGDI2 function. Protein interaction analysis identified Src as a novel RhoGDI2 interaction partner. Gene expression profiling and immunohistochemistry of human tumors revealed that Src levels diminish as a function of bladder cancer stage. In addition, dimini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 31 publications
2
84
1
2
Order By: Relevance
“…In addition to genes involved in EMT, preclinical studies suggest that RHO-GDP dissociation inhibitor 2 (RHOGDI2), the activity of which is regulated by SRC, is a metastasis suppressor in MIBC 173 174 . In contrast to most tumour types, the expression and activation of SRC is highest in NMIBC [174][175][176] , compatible with the activity of RHOGDI2 in these tumours. Further work on the consequences of loss of RHOGDI2 expression implicated endothelin 1 (EDN1) and versican (VCAN) as promoters of an inflammatory environment involving macrophages and the chemokine (C-C motif) ligand 2 (CCL2)-chemokine (C-C motif) receptor 2 (CCR2) signalling axis that is permissive for metastasis 177 178 .…”
Section: Emt and Metastasismentioning
confidence: 76%
“…In addition to genes involved in EMT, preclinical studies suggest that RHO-GDP dissociation inhibitor 2 (RHOGDI2), the activity of which is regulated by SRC, is a metastasis suppressor in MIBC 173 174 . In contrast to most tumour types, the expression and activation of SRC is highest in NMIBC [174][175][176] , compatible with the activity of RHOGDI2 in these tumours. Further work on the consequences of loss of RHOGDI2 expression implicated endothelin 1 (EDN1) and versican (VCAN) as promoters of an inflammatory environment involving macrophages and the chemokine (C-C motif) ligand 2 (CCL2)-chemokine (C-C motif) receptor 2 (CCR2) signalling axis that is permissive for metastasis 177 178 .…”
Section: Emt and Metastasismentioning
confidence: 76%
“…Intriguingly, higher stages seemed to numerically express Src less commonly than lower stages, but statistically significant differences were not found, probably due to the small numbers of tumors per stage. Src expression decreased with higher TCC tumor stage in another recent study, which suggests that its inhibition may be more relevant in patients with lower tumor stages (27). Although the level of activated Src signaling (i.e., p-Src) in human tumor specimens is of great interest, we did not perform these studies due to the lack of fresh or frozen tumor tissue.…”
Section: Discussionmentioning
confidence: 95%
“…However, there is no evidence supporting the expression of other key targets of dasatinib, Kit and Abl, in TCC. Intriguingly, a recent preclinical study suggests the beneficial antimetastatic effect of Src in TCC with the finding that phosphorylation by Src enhanced metastasis suppression by RhoGDI2 (27). Therefore, the further validation of Src as a molecular target at least in a subset of patients with TCC is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…RhoGDI2 belongs to a small family of proteins acting as RhoGTPase inhibitors by reducing dissociation of GDP from Rho proteins. Src interacts with and phosphorylates RhoGDI2 to enhance the metastasis suppressive effects [109]. Recently, Said et al showed that RhoGDI2-deficient disseminated tumor cells secrete several soluble factors (i.e., ECM molecules, versican, CCL2 and IL6) that stimulate macrophage recruitment [110][111][112].…”
Section: Rhogdi2mentioning
confidence: 99%